Analisis Kemampuan Pemahaman Konsep Matematis Siswa Kelas VII pada Materi Bentuk Aljabar - Mareta, Dea; Zulkarnaen, Rafiq (Program Studi Sarjana Pendidikan Matematika, Universitas Singaperbangsa Karawang, 2023)
This study aims to analyze the ability to understand mathematical concepts of grade VII students on algebraic form material. The research subjects were 26 students who were taken purposively at a State Junior High School in Kuningan Regency, West Java Province. The research methods used in this study are case studies with single cases and single analysis. The low ability to understand mathematical concepts of grade VII students as the focus of cases to be analyzed, with case analysis based on understanding mathematical concepts in algebraic form material. Test instruments were used in this study, as many as 8 description questions and 1 multiple-choice to measure students' numeracy skills. The results of the study concluded that the understanding of mathematical concepts is still very low, that is: almost all students can restate the concept of an algebraic form. However, some students do not understand how to classify objects according to their properties, present concepts in the form of mathematical representations, and apply concepts in problem solving.